Gandhi in political theory: Truth law and experiment - Veeravalli, Anuradha (England, 2014)
Despite an overwhelming body of scholarship and literature on his life and thought, the true systematic nature of Gandhi$1 (Bs intervention with modern political theory and his method and structure of thought have not previously received sustained attention. This book attempts to address the lacuna by contending that Gandhi$1 (Bs critique of modern civilization and the presuppositions of post-Enlightenment political theory, its epistemological and metaphysical foundations was both comprehensive and systematic.s
Keywords: Political science-philosophy; Mahatma Gandhi